PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. KULIT MURNI ASIA TENGGARA - Maesaroh Maesaroh; Shinta Bella (Universitas La Tansa Mashiro, 2019)
The background of the problem in this research is the work targets of employees that have not been achieved, the lack of employee interaction with one another in carrying out the tasks of superiors so that the work is less than optimal, the leader is less able to give birth to thoughts for future reach, the leadership lacks motivation for employees , because there are still some employees who are lazy and leave the task during working hours without prior information or permission, the number of problems of employees outside of work that result in lack of concentration in work. This study uses an associative method with a quantitative approach. The population in this study were 120 employees at PT. Southeast Asia Pure Skin. Sampling using slovin formula with a sample size of 40 respondents. The results of this study indicate that leadership style and motivation have a relationship to employee performance, while the contribution of leadership style and work motivation affects employee performance by 40% while the remaining 60% is influenced by other factors not examined by the authors. As for the t test (1) the influence of leadership style on employee performance at PT. Southeast Asia Pure Skin, based on the results of the t test with t count> t table that is (4.968> 2.026), and a significant value of 0.000 <0.05, meaning that there is an influence between leadership style on employee performance, (2) the effect of work motivation on employee performance at PT. Southeast Asia Pure Skin, based on the results of the t test with T count> T table that is (2,460> 2,026), and a significant value of 0.019 <0.05, meaning that there is an influence between work motivation on employee performance. (3) leadership style and work motivation on employee performance based on the results of the f test with the results of the f count> f table that is (12,347> 3,244) with a significance value (0,000 <0,05) meaning that there is a significant influence between leadership style and work motivation simultaneously on employee performance. There is a positive influence between leadership style on employee performance at PT. Southeast Asia pure skin, There is a positive influence between work motivation on employee performance at PT. Southeast Asia pure skin, leadership style and work motivation simultaneously have a significant effect on employee performance at PT. Southeast Asia's pure skin.